Compact laser-driven plasma X-ray source for time-resolved diffraction, spectroscopy and imaging experiments at ELI Beamlines - Pulnova, Y; Parkman, T; Angelov, B; Baranova, I; Zymaková, A; Cipiccia, S; Fardin, L; Yorke, B A; Antipenkov, R; Peceli, D; Hort, O; Mai, D D; et al. (Journal of synchrotron radiation, 2025)
In this work, experimentally measured characteristics of a kilohertz laser-driven Cu plasma X-ray source that was recently commissioned at the ELI Beamlines facility are reported. The source can be driven either by an in-house developed high-contrast sub-20 fs near-infrared terawatt laser based on optical parametric chirped-pulse amplification technology or by a more conventional Ti:sapphire laser delivering 12 mJ and 45 fs pulses. The X-ray source parameters obtained with the two driving lasers are compared. A measured photon flux of the order up to 1012 Kα photons s-1 (4π)-1 is reported. Furthermore, experimental platforms for ultrafast X-ray diffraction and X-ray absorption and emission spectroscopy based on the reported source are described.
Keywords: plasma X-ray sources; time-resolved experiments; laser-driven sources; ELI Beamlines; sub-picosecond sources; ultrafast; Cu Kα lines